Respuesta :

Answer:

Answer is option d) y+1 = 3(x-3)

Step-by-step explanation:

[tex]given \: that \: the \: equation \: is \: parallel \: to \\ y = 3x - 3 \\ 3x - y - 3 = 0 \\ the \: equation \: parallel \: to \: 3x - y - 3 = 0 \: \: is \\ 3x - y + k = 0 \\ since \: it \: passes \: through \: (1, - 1) \\ 3(1) - ( - 1) + k = 0 \\ 3 + 1 + k \: = 0 \\ k + 4 = 0 \\ k= - 4 \\ the \: equation \: parallel \: to \: 3x - y - 3 = 0 \: \\ \: is \: \: 3x - y - 4 = 0 \\ it \: can \: also \: be \: written \: as \: y + 1 = 3(x - 3) \\ hence \: the \: answer \: is \: option \: d[/tex]

HAVE A NICE DAY !

THANKS FOR GIVING ME THE OPPORTUNITY TO ANSWER YOUR QUESTION.